The Universality of Democracy in Economic and Cultural Context - Mustafa Zafer Soydan; Refly Setiawan (Jurnal Cita Hukum, 2022)
Democracy and universality are serious issues that concern everyone today and need to be studied. The question is whether democracy is universal or not remains up-to-date. Those who value democracy say that democracy is universal, while those who do not value democracy say that democracy is not universal. The research method used in this study uses a qualitative method with an empirical normative approach. The results suggest that the relationship between democracy and universality remains uncertain. This uncertainty has spread to the legal, cultural and economic fields. Any subject interested in democracy examines the concept from a hermeneutic and relativist perspective, starting from their own value judgments, and by focusing on the positive and negative aspects of the concept. This further leads to the formation of different tendencies regarding the universality of democracy. This raises the need for a re-evaluation of the concept.Keywords: Universal; Democracy; Law; Culture; Economy Universalitas Demokrasi dalam Konteks Ekonomi dan Budaya AbstrakDemokrasi dan universalitas merupakan isu serius yang menjadi perhatian semua orang saat ini dan perlu dikaji. Pertanyaannya adalah apakah demokrasi itu universal atau tidak tetap up-to-date. Mereka yang menghargai demokrasi mengatakan bahwa demokrasi itu universal, sedangkan mereka yang tidak menghargai demokrasi menyatakan bahwa demokrasi tidak universal. Metode penelitian yang digunakan dalam penelitian ini menggunakan metode kualitatif dengan pendekatan normatif empiris. Hasil penelitian menyatakan bahwa hubungan antara demokrasi dan universalitas tetap tidak pasti. Ketidakpastian ini telah menyebar ke bidang hukum, budaya dan ekonomi. Setiap mata pelajaran yang tertarik dengan demokrasi mengkaji konsep dari hermeneutik dan relativis perspektif, mulai dari penilaian nilai mereka sendiri, dan dengan berfokus pada aspek positif dan negatif dari konsep tersebut. Selanjutnya mengarah pada pembentukan kecenderungan yang berbeda tentang universalitas demokrasi. Hal ini menimbulkan perlunya evaluasi ulang konsep.Kata Kunci: Universal; Demokrasi; Hukum; Budaya; EkonomiУниверсальность демократии в экономическом и культурном контексте АннотацияДемократия и универсальность — это серьезные вопросы, которые волнуют сегодня всех и нуждаются в изучении. Вопрос о том, универсальна ли демократия или нет, остается актуальным. Те, кто ценит демократию, говорят, что демократия универсальна, а те, кто не ценит демократию, говорят, что демократия не универсальна. Метод исследования, использованный в данном исследовании, представляет собой качественный метод с эмпирическим нормативным подходом. Результаты показывают, что связь между демократией и универсальностью остается неопределенной. Эта неопределенность распространилась на правовую, культурную и экономическую сферы. Любой субъект, интересующийся демократией, исследует концепцию с герменевтической и релятивистской точки зрения, исходя из своих собственных оценочных суждений и сосредоточив внимание на положительных и отрицательных аспектах концепции. Это в дальнейшем приводит к формированию различных тенденций относительно универсальности демократии. В связи с этим возникает необходимость переоценки концепции.Ключевые слова: Универсальный; Демократия; Закон; Культура; Экономика